A Novel Nonlinear Chaotic Mapping Based on Cosine-Exponent - Jia, Jinwei; Han, Zhuangzhi; Liu, Limin (2022 IEEE 2nd International Conference on Data Science and Computer Application (ICDSCA), 2022)
Chaotic systems have been widely used in many fields such as information encryption and complex signal modulation in recent years, because of the initial conditions sensitivity in the chaotic systems and the pseudo-randomness of chaotic sequences. Aiming at the problems of low complexity and low randomness of typical one-dimensional chaotic mapping, a new chaotic mapping based on cosine and exponential function is designed in this paper. Simulation results show that the randomness, complexity and balance of the new chaotic map are better than those of the typical one-dimensional chaotic map. And it has a good application prospect.